Effects of Different Types and Levels of Zinc SulphateApplications in Vineyards (Vitis vinifera L.) ina Semi-arid Environment - AYDIN, SENAY; YAGMUR, BULENT; HAKERLERLER, HUSEYIN; COBAN, HARUN (Asian Journal of Chemistry, 2010)
The present study was carried out to determine the effect of soil and foliar applications of different rates of zinc in the vicinity of Alasehir, one of the most important viticultural centres in the Western Aegean Region where the round seedless grape cultivar (Vitis vinifera. L.) is widely grown, on productivity and some chemical quality characteristics as well as leaf primary and secondary elements. Zinc was applied to soil and foliage as ZnSO4·7H2O in the experiment with four replications. One soil application (0-15-30-45 g ZnSO4·7H2O/vine) in addition to foliar application replicated three times (0.0-0.025-0.050-0.10% Zn). Both soil and foliar zinc sulphate (ZnSO4·7H2O) applications increased the amount of fresh grapes per vine. The highest yield was observed at 30 g ZnSO4·7H2O level per vine in soil application and at the rate of 0.05% Zn in foliar application. Zinc sulphate produced a significant positive effect on the contents of primary and secondary elements (N, P, K, Ca, Mg, Fe, Zn, Mn, Cu) of the leaf (lamina and petiole) with the exception of the leaf petiole manganese content in the soil application and the leaf petiole copper content in the foliar application. Soil and foliar applications of zinc sulphate negatively affected the firmness of the berry flesh. The only fruit quality characteristic positively affected by soil and foliar applications of zinc sulphate was the amount of total soluble solids. Despite the fact that the soil application of zinc sulphate did not have any significant effect on some sugar fractions, the foliar application increased only the fructose and α-glucose significantly. In conclusion, it was established that foliar application of zinc sulphate was slightly more effective on yield as well as some quality characteristics as compared to soil application. Therefore, it was concluded that foliar application could be preferred as it is more economical and easier to apply.